LOGISTICS OF TOURISM IN THE LOGISTICS OF SERVICES STRUCTURE: THEORY AND PRACTICE OF THE URBAN TOURISM CASE - Smyrnov I. G. (World Science, 2018)
Theory and practice of tourism logistics in the logistics of services structure are opened. Essence of logistical integrated strategy of sustainable development of urban tourism, based on two concepts - tourism decentralization and reverse logistics is outlined. The first concept is based on logistical organization of the tourist space of the city, which includes such components as: geologistical (geographical and logistical) identification of the resource base of urban tourism; logistical planning of tourist flows and determination of their needs; logistical design of tourist infrastructure; logistical design of supply chains of tourist infrastructure. The second concept involves an integrated approach to the recycling of the total amount of urban waste, including tourist one, taking into account their collection and removal from the city, as well as processing at special enterprises. The experience of Ukrainian cities of Lviv and Kyiv in this context is considered.